Resíduos de serviços de saúde: gerenciamento em rede de monitoramento à luz da responsabilidade socioambiental - Braga, Lígia de Oliveira (2018)
The Health Services are generators of waste that can be dangerous, depending on their classification, being a public and environmental health problem when handled improperly. The National Sanitary Surveillance Agency (ANVISA) and the National Environment Council (CONAMA) have resolutions that regulate and define guidelines for correct management. Sustainable management models are required in the institutions that generate these residues, considering aspects and characteristics that can be monitored in monitoring networks, with a view to advancing the quality of management incorporating socioenvironmental responsibility in their operation. Therefore, it is necessary to develop research aimed at this management, favoring the reduction of this waste and mitigating the possible aggressions to the environment and public health, thus assisting public power and health professionals. In order to guide this thesis, the general objective is to propose a model of Health Services Waste Management based on monitoring networks in the perspective of Socio-Environmental Responsibility. The research had its theoretical-methodological bases regarding the objectives (exploratory-descriptive), procedures (documentary and bibliographic research) and data analysis (quantitative, qualitative and content analysis). As a result, four states that formalize the PGRSS model as a management tool for generating services are searched in the websites of the respective Health Secretariats, which was not evidenced in relation to ANVISA and other states and the Federal District. This situation makes explicit the need to improve these records, to promote inspection and formalization of production information, which can be carried out through monitoring networks, which allows the existence of a flow of data between municipalities, states and federal level, so that actions and interventions can be planned and carried out with real data base, since, currently, the sources that exist, most of the times, are by self-declaration of the generators. The model in monitoring networks promotes information obtained from those generated, supervised and monitored by the supervisory bodies, in the three spheres of government (municipal, state and federal) giving subsidies to the public power and the stakeholders in the process with analyzes and actions allowing improvements in management quality.